MANIFESTASI ORAL PADA PASIEN TERINFEKSI VIRUS HIV/AIDS - Sri Ramayanti (Andalas Dental Journal, 2013)
Acquired immunodeficiency syndrome (AIDS) epidemic is increasing all over the world. The first AIDS case in Indonesia was found in 1987 in Bali, but the spread of HIV in Indonesia increased after 1995. Based on data from the Ministry of Health until the year 2012 as many as 21 511 cases of HIV and AIDS as many as 5,686 people and the number of patients who died as many as 1,146 people. This literature study aims to describe the oral manifestations in HIV-infected patients and its management. Oral lesions are most commonly found in HIV-infected patients is candidiasis. Other oral lesions that might be found that necrotizing ulcerative gingivitis, linear gingival erythema, hairy leukoplakia, Kaposi's sarcoma, herpes simplex virus infections, Recurrent Aphthous Ulcers, Varicella Zoster Virus (VZV), Citomegalo Virus (CMV), Human Papilloma Virus (HPV), Condyloma Akumilatum, Lymphoma Non-Hodgkins B-cell and squamous cell carcinoma, and Sarcoma Kapossi. The best management is through preventive measures and oral routine exam to maintain oral health and achieve a better quality of life.